ASSESSMENT OF QUALITY OF LIFE AND SOCIAL ADAPTATION OF PATIENTS WITH EPILEPSY - Abdullaev, J. D.; Ataniyazov, M.K. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Epilepsy is a chronic neurological disease characterised by repeated attacks of excessive electrical activity in the brain, which significantly affects the quality of life of patients. This review article analyses modern approaches to assessing the quality of life and social adaptation of patients with epilepsy, with an emphasis on clinical methods and psychological diagnostic tools. A review of research over the past 10 years found that optimised pharmacotherapy, including polytherapy and the use of drugs such as lamotrigine, improves the quality of life for patients. Monotherapy with anticonvulsants also shows positive results, but seizure control is insufficient without taking into account side effects, psycho-emotional disorders and the level of social adaptation. Research has shown that psychological defence mechanisms, cerebrospinal fluid index (CSI) and family environment play an important role in the quality of life of patients with epilepsy.